Maintenance of renal function in a patient with a history of acute paroxysmal nocturnal hemoglobinuria-associated kidney injury. Issue 3 (2nd March 2018) - Re, Francesca; Manfra, Ilenia; Russo, Filomena; Plenteda, Caterina; Spolzino, Angelica; Follini, Elena; Gullo, Maria; Romano, Claudia; Baroni, Maria Cristina; Aversa, Franco
Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, life-threatening blood disorder characterized by intravascular hemolysis, thrombosis and bone marrow failure. Acute kidney injury, including acute renal failure, have been reported in patients with PNH. We report the case of a 36-year-old male patient with PNH who developed acute kidney injury following an infection of undetermined diagnosis. Although hemolysis was initially controlled and renal function stabilized following packed red blood cell transfusion and empirical levofloxacin and prednisone, he later experienced recurrent episodes of hemolysis and hematuria requiring monthly red blood cell support. Given the high risk of thromboembolic events, treatment with standard-dose eculizumab was started. The patient's hematologic values improved, renal function was maintained, and no thromboembolic events occurred.